HANDOVER DALAM KOMUNIKASI BERGERAK SELULER - Paronda, Abdul Hafid (RESULTAN : Jurnal Kajian Teknologi, 2010)
Hand-off is the transfer of a call from one cell site to another as the cellular phone moves through the service coverage area. The cell site warns the MTSO that the mobile?s signal strength is falling below a predetermined level. The MTSO then alerts all cell sites bordering on the first one. They measure the mobile?s transmitting signal and report back to the MTSO. The MTSO, which is programmed to select the site receiving the strongest signal, then switches the call from the weak cell to the strongest cell without interrupting the call. The whole process takes a fraction of a second, and the caller usually is unaware of it. Such hand-offs may occur several times during a single conversation as the caller moves through the coverage area